The Effect of Independent Board of Commissioners, Inventory, and Fixed Asset Intensity on Tax Aggressiveness - Cahyani, Indah Duwi; Ridho, Muhammad (Jurnal Rekognisi Akuntansi, 2024)
This study aims to investigate and evaluate the effect of independent board of commissioners, inventory intensity, and fixed asset intensity on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The approach used in this study is quantitative, with secondary data obtained from financial reports and annual reports of companies listed during the period. The research population includes all property and real estate companies listed on the IDX during that period. The sampling technique used was purposive sampling, where samples were selected based on certain criteria, resulting in 27 samples and 81 observation data. The analysis methods applied include descriptive statistical analysis, multiple linear regression, model feasibility test, hypothesis testing, and classical assumption testing. The research findings show that the independent board of commissioners and inventory intensity have a significant positive effect on tax aggressiveness, while fixed asset intensity has a negative and significant effect on tax aggressiveness